Telomere length is not associated with frailty in older Chinese elderly: Cross-sectional and longitudinal analysis. (December 2015) - Yu, Ruby; Tang, Nelson; Leung, Jason; Woo, Jean
Highlights: This study examines the association between telomere length and frailty in a prospective study over five years of 2006 men and women aged 65 years and older living in the community. Frailty was defined according to the Fried criteria. Telomere length was not associated with frailty, neither cross-sectionally nor longitudinally. Follow-up studies are needed to evaluate telomere attrition and its relationship with different stages of frailty. Abstract: Telomere shortening has been associated with biological age and several chronic degenerative diseases. However, less is known about telomere length and frailty, which is an indicator of biological age. This study examines the association between telomere length and frailty in a prospective study over five years of 2006 men and women aged 65 years and older living in the community. The frailty status was determined by the Fried's criteria. Telomere length in leukocytes was measured using the quantitative polymerase chain reaction. Logistic regression was used to examine the association between telomere length and incidence of frailty. Among 2006 subjects (mean age 72.4 ± 5.1 years, 51.3% women), the mean telomere length at baseline was 9.1 ± 2.0 kb and the frailty phenotype was detected in 127 subjects (6.3%). Male gender was related to shorter telomere length, with increased years of age related to a shortened telomere length ( P < 0.05). In both men and women, no statistically significant difference of telomere length and the frailty phenotype was observed at baseline. After 4 years of follow-up, 116 cases of frailty were identified. There was no association between telomere length and incident frailty. In conclusion, telomere length was not associated with frailty in this study population.